Analisis Potensi Energi Listrik dan Ekonomis Biogas dari Ampas Kelapa Provinsi Riau: Analisis Potensi Energi Listrik dan Ekonomis Biogas dari Ampas Kelapa Provinsi Riau - Nanda Putri Miefthahwati nanda (Institut Riset dan Publikasi Indonesia, 2025)
BPS data from 2021 states that coconut production in Indonesia is the largest in the world, with a total production of 988.3 thousand tonnes of coconuts. The largest coconut production comes from Riau Province, with a production of 1,100 tonnes. Generally, coconuts are used to make coconut milk, leaving behind coconut pulp as waste. This waste is considered garbage because it no longer has any beneficial value, so it is disposed of directly. This disposal has an impact on the environment because biomass waste that is disposed of directly will cause a foul odour and methane gas emissions that are 20 times more harmful than CO2 emissions, even though coconut husk waste contains nutrients that can be processed into a new energy source in the form of biogas. This research aims to analyse the biogas potential that can be generated from coconut husk waste, including the potential for electricity generation and its economic analysis. This research uses the anaerobic respiration method to produce biogas in an anaerobic digestion reactor simulated using the SuperPro Designer application. From the research conducted, it was found that the potential biogas that can be produced from coconut husk waste in a year in Riau Province is 15,321,231.9 m3, which is obtained from 134 tonnes of coconut husk waste in Riau Province in 2021. In addition, the biogas produced is capable of generating 141,703,473 kWh of electricity per year, with a potential revenue of Rp. 212,555,209,500 and an annual profit of Rp. 163,532,903,700. With a B/C ratio of 1.26 and a payback period of 9.6 months, it can be said that this investment is profitable and feasible to be realised. Keyword: Biogas, Coconut Waste, Electricity, Economics.